Traumas e travessias: a alteridade ameríndia e as fronteiras simbólicas da nação - Rita Olivieri-Godet (Universidade de Brasília, 2012)
Examination of issues related to the processes of extinguishment and retrieval of memory, through fictional texts dealing with both identity negotiations and cross- ings of cultural frontiers, focusing on Amerindians as instances of alterity.